RESTRUCTURING AS A PART OF COMPANY CRISIS MANAGEMENT - Fedorková, Katarína; Czillingová, Jana (European Scientific Journal, ESJ, 2014)
Company crisis management. Company bankruptcy. Causes of company bankruptcy. Solution of bankruptcy. Bankruptcy and restructuring. Informal restructuring and restructuring under supervision of the court. When to execute restructuring. Restructuring in the Slovak republic compared to restructuring in the Czech republic. Comparison of advantages and disadvantages of restructuring proceedings conditions in the Slovak and conditions in the Czech Republic. Differences restructuring proceedings in the Slovak Republic and the Czech Republic.